THE IMPLEMENTATION OF THE POSKESTREN PROGRAM AT DARUL HUFFAZH ISLAMIC BOARDING SCHOOL, PESAWARAN REGENCY, IN 2025 - Wahyudi, Anang; Riyanti, Riyanti; Perdana, Agung Aji (HEARTY, 2026)
The Islamic Boarding School Health Post (Poskestren) is a form of community-based health effort (UKBM) implemented within Islamic boarding schools, based on the principle of being initiated by, from, and for the pesantren community. Poskestren plays a significant role in delivering promotive and preventive health services, without neglecting curative and rehabilitative aspects. Preliminary observations at Darul Huffazh Islamic Boarding School revealed that self-assessment surveys and community discussions—activities that should be conducted routinely—had only been held once, at the beginning of the Poskestren establishment. This gap has resulted in the absence of reports related to personal hygiene improvement, environmental health, and students’ health literacy, both at the pesantren and the local community health center (Puskesmas). Moreover, the number of health cadres—only nine for a total of 450 students—does not meet the proportional standard stated in the Poskestren implementation guidelines. This study aimed to analyze the implementation of the Poskestren program at Darul Huffazh Islamic Boarding School, Pesawaran Regency. A qualitative descriptive method was employed, involving seven informants, including pesantren administrators, Poskestren staff, health cadres, and students. The findings indicate that most input, process, and output indicators were adequately fulfilled, such as the availability of health cadres, facilities, policy support, and funding. The implementation process—covering planning, execution, and evaluation—was in place, although supervision from Puskesmas officers remained suboptimal. The program outcomes showed improvements in students’ health knowledge and clean and healthy living behavior (PHBS). In conclusion, the Poskestren program at Darul Huffazh has been implemented fairly well, although further efforts are needed to strengthen cross-sectoral guidance and improve health facilities.